Endothelial function and lipid peroxidation in patients with arterial hypertension and its cerebral complications - M. V. Kazak; T. S. Romanenko; M. G. Omelyanenko; A. V. Lebedeva; I. K. Tomilova; V. N. Vyatkin; A. V. Kontsevaya (Кардиоваскулярная терапия и профилактика)
Aim. То assess endothelial function (EF) and lipid peroxidation (LPO) in patients with arterial hypertension (AH) and its cerebral complications.Material and methods. In total, 49 patients with ischemic stroke (IS), 37 patients with uncomplicated essentialAH (EAH) and 25 blood donors as controls were examined. NO concentration (its stable metabolites, nitrates and nitrites) was measured by Griss method; citrulline (C) and malonic dialdehyde (MDA) levels were assessed with photocolorimetric method. Desquamated endotheliocytes (DE) were counted according to the method by J. Hladovec. LPO and plasma antioxidant activity (AOA) were studied with biochemiluminescence analysis.Results. In IS patients, NO and C concentrations were lowerthan inAH patients and controls, while DE numbers were higher in the former. These parameters were combined into one factor, “integral index of endothelial dysfunction” (IIED), with values of -0,86±0,19, 0,12±0,09, and 1,21±0,23 units in patients with IS, AH and in controls, respectively (p<0,005). LPO intensity was higher in IS individuals than in the controls; the same was true for MDA levels. AOA in IS subjects was similar to that in the control group. IIED was significantly correlated with LPO intensity and MDA concentration in IS patients.Conclusion. UncomplicatedAH was characterised by compensated endothelial dysfunction, while NO-endothelium system was decompensated in stroke. IIED parameter, representing EF in general, encompassed NO and C concentrations as well as DE count. In stroke patients, LPO activation was not associated with compensatory increase in AOA Endothelial dysfunction and LPO were strongly correlated.